Was macht es, wo die Kategorien herkommen? - Robert Ziegelmann (Recherches Germaniques)
In order to understand how Alfred Sohn-Rethel’s proposal differs from Kant’s, the author first develops a plausible version of Sohn-Rethel’s interpretation of the relation between the genesis and validity of categories in Kant’s thought. Two ways then seem to open up for Sohn-Rethel’s counter-proposal: Either the validity of categories is limited to societies in which commodity exchange is predominant by way of a consensus theory of truth, or their origin simply does not affect their validity. The author proposes to read Sohn-Rethel’s theory as an explanation and a critique of the colonisation of lifeworld ontologies by abstractions derived from natural science practices.